1995
DOI: 10.1128/mcb.15.9.5071
|View full text |Cite
|
Sign up to set email alerts
|

The DuplicatedSaccharomyces cerevisiaeGeneSSM1Encodes a Eucaryotic Homolog of the Eubacterial and Archaebacterial L1 Ribosomal Proteins

Abstract: A previously unknown Saccharomyces cerevisiae gene, SSM1a, was isolated by screening for high-copy-number suppressors of thermosensitive mutations in the RNA14 gene, which encodes a component from the polyadenylation complex. The SSM1a gene codes for a 217-amino-acid protein, Ssm1p, which is significantly homologous to eubacterial and archaebacterial ribosomal proteins of the L1 family. Comparison of the Ssm1p amino acid sequence with that of eucaryotic polypeptides with unknown functions reveals that Ssm1p is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 69 publications
3
46
0
Order By: Relevance
“…As previously shown, Pab1p was found throughout the gradient as both a soluble and a polysome-associated protein (24). Ssm1p, a 60S ribosomal subunit protein (33), was detected in fractions containing the free 60S subunit and in the polysomes. Nam1p, a mitochondrial contaminant, was present essentially in the upper fractions with the soluble proteins.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…As previously shown, Pab1p was found throughout the gradient as both a soluble and a polysome-associated protein (24). Ssm1p, a 60S ribosomal subunit protein (33), was detected in fractions containing the free 60S subunit and in the polysomes. Nam1p, a mitochondrial contaminant, was present essentially in the upper fractions with the soluble proteins.…”
Section: Resultsmentioning
confidence: 56%
“…Polysome extracts were prepared as previously described from cells grown to an optical density at 600 nm (OD 600 ) of between 0.6 and 0.8 and clarified by centrifugation at 20,000 ϫ g for 20 min. Extracts were fractionated through 5 to 50% sucrose gradients by centrifugation at 39,000 rpm, for 3 h, at 4°C in a Beckman SW41 rotor and analyzed by monitoring the A 260 (33). Cycloheximide was omitted from the culture medium before cell harvesting, and the extraction buffer and sucrose gradients were as indicated in the text below.…”
Section: Methodsmentioning
confidence: 99%
“…4B). Although RPL1A encodes the identical protein, it is expressed at much lower levels (Petitjean et al 1995), and the rpl1a-Δ mutant does not exhibit this phenotype (data not shown). …”
Section: Read-through Of Cga Codons Is Improved By Treatment With Parmentioning
confidence: 99%
“…Ten picomoles of oligonucleotide 8238, GATGTTCAAACAACCTGGGC, or 1834 (29) was 5Ј end labeled with 25 Ci of g-32P ATP by using T4 polynucleotide kinase. The hybridization was performed at 37°C for 12 h. The membrane was washed three times for 5 min at 25°C and for 15 min at 42°C.…”
Section: Methodsmentioning
confidence: 99%